PELAKSANAAN KURIKULUM 2013 DI SMP NEGERI 4 BANJARMASIN - Akhmad Riyadi (JURNAL SOCIUS, 2018)
AbstractCurriculum changes KTSP 2006 to Curriculum 2013 raises new problems for the community, for schools and for teachers due to lack of socialization and readiness in the field, therefore this study aims to find out about the Implementation of Curriculum 2013 at State Junior High School 4 Banjarmasin, more specifically want to know how readiness schools in the socialization of the Curriculum 2013, the readiness of infrastructure facilities supporting the implementation of Curriculum 2013, and the readiness of teachers in implementing Curriculum 2013. Research methods that researcher used is Qualitative-Descriptive with Data collection through interviews, observation, and documentation, then analyzed data include three procedures: (1) reduction, (2) data presentation; (3) drawing conclusions and verification. The result of the research shows that: (1) The school has prepared the planning and organizing socialization of the implementation of Curriculum 2013 at State Junior High School 4 Banjarmasin through training activities of In House Training (IHT) and Subject Teacher Consultant; (2) The school has also prepared infrastructure supporting the implementation of Curriculum 2013, such as package books, learning media, computer, internet, LCD, etc .; (3) The teacher has implemented the 2013 Curriculum Learning with the Scientific Approach which is described in the observation result of Social Science study in class VII well. The conclusion of at State Junior High School 4 Banjarmasin study has been ready to implement the Curriculum 2013 with the fulfillment of the three indicators of the research results.Keywords: Implementation, Curriculum 2013, and Junior High School AbstrakPerubahan kurikulum KTSP 2006 menjadi Kurikulum 2013 memunculkan masalah baru baik bagi masyarakat, bagi sekolah maupun bagi guru karena kurangnya sosialisasi dan kesiapan di lapangan, karena itu penelitian ini bertujuan mencari tahu tentang Pelaksanaan Kurikulum 2013 di SMP Negeri 4 Banjarmasin, lebih rinci lagi ingin mengetahui bagaimana kesiapan sekolah dalam sosialisasi Kurikulum 2013, kesiapan sarana prasarana penunjang pelaksanaan Kurikulum 2013, dan kesiapan guru dalam melaksanakan Kurikulum 2013. Metode penelitian yang peneliti gunakan adalah Kualitatif-Deskriptif dengan Pengumpulan data melalui wawancara, observasi, dan dokumentasi, selanjutnya data dianalisis meliputi tiga prosedur yaitu: (1) reduksi, (2) penyajian data; (3) penarikan kesimpulan dan verifikasi. Hasil penelitian yang diperoleh menunjukkan bahwa: (1) Sekolah sudah mempersiapkan perencanaan dan pengorganisasian sosialisasi pelaksanaan Kurikulum 2013 di SMP Negeri 4 Banjarmasin melalui kegiatan pelatihan Workshop/In House Training (IHT) dan Musyawarah Guru Mata Pelajaran (MGMP); (2) Sekolah juga sudah mempersiapkan sarana prasarana penunjang pelaksanaan Kurikulum 2013, seperti buku paket, media pembelajaran, komputer, internet, LCD, dll; (3) Guru sudah melaksanakan Pembelajaran Kurikulum 2013 dengan Pendekatan Saintifik yang terdeskripsikan dalam hasil observasi pembelajaran IPS di kelas VII dengan baik. Kesimpulan penelitian SMP Negeri 4 Banjarmasin telah siap melaksanakan Kurikulum 2013 dengan terpenuhinya ketiga indikator hasil penelitian tersebut.Kata Kunci : Pelaksanaan, Kurikulum 2013, SMP Negeri